Optimum tuning of Unified Power Flow Controller (UPFC) via Ant Colony Optimization (ACO) technique / Zulkiffli Abdul Hamid - Abdul Hamid, Zulkiffli (2010)
Unified Power Flow Controller (UPFC) is a Flexible Alternating Current Transmission System (FACTS) device that can control the power flow in transmission lines by injecting active and reactive voltage components in series with the lines using power converter modules, based on an externally dc-link voltage. As the power flow has been controlled, this device is capable of minimizing the overall system losses and simultaneously improves the voltage stability. To be able effectively control the power flow so that losses and voltage stability are at optimum level, UPFC parameters need to be tuned by using optimization algorithm. This thesis describes how Ant Colony Optimization (ACO) technique can be used to tune the parameters of FACTS device in order to improve power system performance. ACO is a new cooperative agent's approach, which is inspired by the observation of the behaviors of real ant colonies on the topics of ant trial formation and foraging method. The algorithm was implemented in MATLAB applied to the IEEE-30 Bus Reliability Test System (RTS). Comparative studies were conducted based on performance of UPFC in terms of their number and locations for installations in power system. The outputs obtained from the study revealed that the proposed technique gave promising results.